2016
DOI: 10.1016/j.respol.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Science and Technology Parks and cooperation for innovation: Empirical evidence from Spain

Abstract: Science and Technology Parks (STPs) are one of the most important regional innovation policy initiatives. Previous studies show that location in a Park promotes cooperation for innovation but have not investigated if they help to achieve better results from cooperation. We extend previous literature by analyzing how STPs influence the results of cooperation of Park firms and how this influence is channelled. We rely on a much larger sample of firms and STPs than previous studies and account for selection bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 49 publications
(18 reference statements)
2
74
1
1
Order By: Relevance
“…We can find also similar results when it comes to the STPs literature. Vásquez-Urriago et al [86] analyzed previous studies on STPs which show that the location in a park promotes cooperation for innovation. They demonstrated that STPs are important for fostering innovation cooperation.…”
Section: Clusters and Stpsmentioning
confidence: 99%
“…We can find also similar results when it comes to the STPs literature. Vásquez-Urriago et al [86] analyzed previous studies on STPs which show that the location in a park promotes cooperation for innovation. They demonstrated that STPs are important for fostering innovation cooperation.…”
Section: Clusters and Stpsmentioning
confidence: 99%
“…[ 84,85] Classical market logic Competition under clear rules; profit maximization; cost reduction; free enterprise; individualism; short-termism. Control of data is a source of competitive advantage.…”
Section: Innovation Logicmentioning
confidence: 99%
“…On the other hand, for the province-level HIDZ who intends to apply for state-level upgrade in China, except for the economic performance and development potential, the scientific research level of the local higher education institutions should also be included in the evaluation criterion of the upgrade qualification. Thus, in order to upgrade the province-level HIDZ, the local governments would be motivated to raise the scientific research level of higher education institutions in the cities, and this will help to achieve a virtuous cycle of regional innovation and development [35].…”
Section: Conclusion and Discussionmentioning
confidence: 99%